The Response Of American Police Agencies To Digital Evidence - Yesilyurt, Hamdi (2011)
Little is known about the variation in digital forensics practice in the United States as adopted by large local police agencies. This study investigated how environmental constraints, contextual factors, organizational complexity, and organizational control relate to the adoption of digital forensics practice. This study integrated 3 theoretical perspectives in organizational studies to guide the analysis of the relations: institutional theory, contingency theory, and adoption-of-innovation theory. Institutional theory was used to analyze the impact of environmental constraints on the adoption of innovation, and contingency theory was used to examine the impacts of organizational control on the adoption of innovation. Adoption of innovation theory was employed to describe the degree to which digital forensics practice has been adopted by large municipal police agencies having 100 or more sworn police officers. The data set was assembled primarily by using Law Enforcement Management and Administrative Statistics (LEMAS) 2003 and 1999. Dr. Edward Maguire`s survey was used to obtain 1 variable. The joining up of the data set to construct the sample resulted in 345 large local police agencies. The descriptive results on the degree of adoption of digital forensics practice indicate that 37.7% of large local police agencies have dedicated personnel to address digital evidence, 32.8% of police agencies address digital evidence but do not have dedicated personnel, and only 24.3% of police agencies have a specialized unit with full-time personnel to address digital evidence. About 5% of local police agencies do nothing to address digital evidence in any circumstance. These descriptive statistics indicate that digital evidence is a matter of concern for most large local police agencies and that they respond to varying degrees to digital evidence at iv the organizational level. Agencies that have not adopted digital forensics practice are in the minority. The structural equation model was used to test the hypothesized relations, easing the rigorous analysis of relations between latent constructs and several indicator variables. Environmental constraints have the largest impact on the adoption of innovation, exerting a positive influence. No statistically significant relation was found between organizational control and adoption of digital forensic practice. Contextual factors (task scope and personnel size) positively influence the adoption of digital forensics. Structural control factors, including administrative weight and formalization, have no significant influence on the adoption of innovation. The conclusions of the study are as follows. Police agencies adopt digital forensics practice primarily by relying on environmental constraints. Police agencies exposed to higher environmental constraints are more frequently expected to adopt digital forensics practice. Because organizational control of police agencies is not significantly related to digital forensics practice adoption, police agencies do not take their organizational control extensively into consideration when they consider adopting digital forensics practice. The positive influence of task scope and size on digital forensics practice adoption was expected. The extent of task scope and the number of personnel indicate a higher capacity for police agencies to adopt digital forensics practice. Administrative weight and formalization do not influence the adoption of digital forensics practice. Therefore, structural control and coordination are not important for large local police agencies to adopt digital forensics practice. v The results of the study indicate that the adoption of digital forensics practice is based primarily on environmental constraints. Therefore, more drastic impacts on digital forensics practice should be expected from local police agencies’ environments than from internal organizational factors. Researchers investigating the influence of various factors on the adoption of digital forensics practice should further examine environmental variables. The unexpected results concerning the impact of administrative weight and formalization should be researched with broader considerations